Technology and Unemployment : A Comparative Study - Blum, Albert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
In this paper, the author summarizes how countries try to prevent job losses caused by technological change and how they assist workers who are discharged as a result of new machines.